Sports law and policy in the European Union - Parrish, Richard (European Policy Research Unit series., 2003)
The commercialisation of sport in Europe raises important questions concerning the most appropriate method of regulating sporting activity. The development of the European Union and the internationalisation of sporting competition has added an internation.